The Development Model of Community Products from Local Textile Wisdom Using for Commerce - Sornnoey, Keeratiya; Kaewsritong, Jiraphat (Arts of Management Journal, 2023)
In this article, a community product creation methodology based on local commercial woven fabric expertise is developed and evaluated. Participatory research methods, such as documented studies, in-depth interviews, and the sample group consisted of a small group of 20 professionals meeting with a smaller group of 20 people chosen at random, as well as a group of satisfaction raters and a group of community representatives. A total of 30 people were obtained by randomization. There are three steps in the research process: 1) Research the fundamentals; 2) Develop and improve a model; 3) Formal evaluation Interview forms, questionnaires, and suitability assessment forms were the instruments employed for data collection. Using descriptive statistics of the research findings, the qualitative data assessed the content and quantitative data. 1) There are nine components in the 3M-Pluses Model for creating community products from locally woven fabrics for commercial usage, including 1) manpower; 2) management; 3) marketing; 4) participation; 5) learning; and 6) uniqueness; 7) standard; 8) evaluation; and 9) sustainability. 2) The model's testing period has ended. The product has satisfied three product certifications. The evaluation of the model's applicability was determined to be at the highest level, and those who are interested in a high level of woven fabric producers and processing groups are content with joining the pattern at the highest level.